Optimizing Risk-based Stock Return Prediction in Tehran Stock Exchange industries: A Data Envelopment Analysis - Hamidreza Akhbari; Heydar Mohammadzadeh Salteh; Rasoul Baradaran Hassanzadeh; Mehdi Zeynali (تحقیقات مالی)
ObjectiveInvestment, the choice of assets to maintain and earn more for future prosperity, is one of the most important issues in the economy of all countries, commanding attention from individuals and high-ranking officials alike. Enhancing stock returns through forecasting is a critical concern in capital markets, necessitating attention from both individual and institutional investors. Accordingly, the present study aims to optimize the forecast of risk-based stock returns in selected industries of the Tehran Stock Exchange. MethodsData analysis was performed in two phases. In the first phase, the data were estimated using a combined data method and AR (1) autoregressive process, from 2010 to 2019. This model forecasts stock returns for selected industries on the stock exchange. In the second stage, using Data Envelopment Analysis (DEA), stock return forecast optimization by the previous stage was optimized for selected industries of the Tehran Stock Exchange from 2010 to 2019. ResultsThe results of optimization of stock return forecast in three industries of oil and gas extraction except exploration, extraction of metal ores and petroleum products revealed that the oil and gas extraction industry, except exploration, exhibited a higher efficiency of 0.4214 compared to other industries. The metal ore mining industry with an efficiency of 0.3728 stood in second place and the petroleum products industry with an efficiency of 0.2516 ranked in third place in terms of efficiency. ConclusionTherefore, it can be said that optimizing stock return prediction in the oil and gas extraction industry, excluding exploration, is at a higher level compared to other industries examined in this study. Given the oil industry's higher efficiency and optimization within the country, it is feasible to integrate oil into the production cycle using effective methods and introduce technological advancements to enhance oil supply within the country. This is particularly viable as the production output of other industries is significantly lower compared to these three industries. basic measures should be taken to increase the production of industrial and non-oil goods to reduce imports and increase exports of final goods to other countries to increase economic growth. Hence, it is recommended to utilize the oil and gas extraction industry, excluding exploration, for the production of final goods, followed by leveraging other industries for further production of final goods. Also, since the oil products industry is influenced by more variables in predicting stock returns, it is recommended that investors in the oil products industry be aware of the variables studied in this research, especially the industrial production growth rate, and consider their stock returns and investment levels accordingly. Future research should explore and assess the optimization of stock return forecasting in other significant industries like pharmaceuticals, electricity, steam, hot water supply, etc. to compare and evaluate their outcomes alongside the findings of this study.